The Influence of Gadget Use on Student Learning Achievement in Elementary Schools - Putri, Icha Kurnia; Nathania, Annisa; Putri, Yuninda; Supriyadi, Supriyadi; Hermawan, Jody Setya (Universitas Muhammadiyah Sumatera Utara, 2024)
This study aims to analyze the effect of gadget use on student learning achievement in elementary schools. In today's digital era, the use of gadgets is increasingly widespread among children, including elementary school students. The method used in this study is descriptive qualitative, This descriptive study is based on the results of relevant data or documentary sources that we have collected. The bibliographic sources of this study are the internet, scientific journals, articles, books and dissertations of experts or previous authors. The results of the analysis show that there is a significant relationship between gadget use and student learning achievement. Students who use gadgets excessively tend to have lower learning achievement compared to those who use gadgets moderately. This study concludes that although gadgets can be a learning aid, their use must be balanced with supervision and limitations so as not to interfere with the learning process. Recommendations for parents and educators are the importance of regulating the time of gadget use to support student learning achievement.